A multi-source flow model for CCS pipeline transportation networks. (December 2015) - Brown, Solomon; Mahgerefteh, Haroun; Martynov, Sergey; Sundara, Vikram; Dowell, Niall Mac
Highlights: A multi-source flow model for predicting the flow in pipeline networks is presented. The model accounts for all pertinent phenomena and variations in feed flow rate. The model is applied to a hypothetical network, including ramp up or down scenarios. Abstract: As part of the operation of the carbon capture and storage process, there are clear practical and economic incentives in employing an integrated pipeline network system involving the capture of CO2 from multiple emission sources such as power plants or steel works followed by injection into a single storage site. This paper presents the development and testing of multi-source flow model for predicting the entire flow conditions such as pressure, temperature, fluid phase and CO2 composition throughout the pipeline network and the delivery to the storage site. The model also accounts for pipeline elevation and periodic variations in feed source flow rate, for example as a result of the ramping up or ramping down of power production from coal fired power stations connected to the pipeline network. The ability to produce the above information is of vital importance given the large impact of the stream impurities on the CO2 phase behaviour and their physiochemical interactions with the pipeline material of construction, compressor power requirements and the storage reservoir performance.